A STUDY ON HRD IN EDUCATION SECTOR - CHALLENGES IN SELFFINANCE COLLEGES - M, Sangeetha.; Mageswari T, Uma; Unnikrishnan, Shruthi (International Journal of Psychosocial Rehabilitation, 2020)
Human resource management in the education industry is a very important result with bandaging the threat of managing challenges against staff turnover. This is because education personnel’s are the major instrument for achieving educational goals, consequently the introduction of new institutions and institution development. Human resources are the key to expressing socio-economic development and efficient service delivery. This paper scheme with staff satisfactory level, developing skills, priority focus, and motivated workforce operating within a maintenance human resource in the same institution. Every educational system depends heavily on the human resources for execution of its program. The function of human resource management in education includes recruitment to retirement of staff, maintenance and development of staff procurement, and their job performance reward. The challenges of human resource management include poor working conditions, problems of staffing, funding, and incessant transfer of staff.